Study the Effectiveness of Patient’s Monitoring in Hospitals Using Wireless Body Sensor Networks - القبيلي مثنى (Latakia University Journal -Engineering Sciences Series, 2020)
Telehealth is a promising technology in its effectiveness, accuracy and prevalence, and given the importance of medical care and monitoring in areas that lack adequate medical staff or are difficult to access on the one hand, and as a result of the high costs of medical treatment, especially for the elderly on the other hand. Wireless body sensor networks (WBAN) has received a lot of attention from research and development, especially as a result of the tremendous development in wireless sensor networks and modern electronics that have caused smart small size sensors that can be positioned inside or on the body. In our research, we will discuss the use of these modern networks in the medical field, in particular patient monitoring in hospitals, as continuous monitoring and control of vital parameters here are of great importance to patients’ lives. The basic idea is to publish a group of sensor devices with a specific formation on the patient’s body, and these devices have several functions to perform the integrated work of measuring and sensing important parameters, and send them as information to a coordinated node that collects these data and sends them to a main station that processes this information and makes decision. Then, it sends a message of this decision to the deployed agencies that translate this decision in order to adjust the parameters again.